Eddy and tidal driven basal melting of the Totten and Moscow University ice shelves - Xia, Yuwei; Gwyther, David E.; Galton-Fenzi, Ben; Cougnon, Eva A.; Fraser, Alexander D.; Moore, John C. (Frontiers in Marine Science, 2023)
The mass loss from the neighboring Totten and Moscow University ice shelves is accelerating and may raise global sea levels in coming centuries. Totten Glacier is mostly based on bedrock below sea level, and so is vulnerable to warm water intrusion reducing its ice shelf buttressing. The mechanisms driving the ocean forced sub-ice-shelf melting remains to be further explored. In this study, we simulate oceanic-driven ice shelf melting of the Totten (TIS) and Moscow University ice shelves (MUIS) using a high spatiotemporal resolution model that resolves both eddy and tidal processes. We selected the year 2014 as representative of the period 1992 to 2017 to investigate how basal melting varies on spatial and temporal scales. We apply the wavelet coherence method to investigate the interactions between the two ice shelves in time-frequency space and hence estimate the contributions from tidal (<1.5 days) and eddy (2-35 days) components of the ocean heat transport to the basal melting of each ice shelf. In our simulation, the 2014 mean basal melt rate for TIS is 6.7 m yr-1 (42 Gt yr-1) and 9.7 m yr-1 (52 Gt yr-1) for MUIS. We find high wavelet coherence in the eddy dominated frequency band between the two ice shelves over almost the whole year. The wavelet coherence along five transects across the ice shelves suggests that TIS basal melting is dominated by eddy processes, while MUIS basal melting is dominated by tidal processes. The eddy-dominated basal melt for TIS is probably due to the large and convoluted bathymetric gradients beneath the ice shelf, weakening higher frequency tidal mode transport. This illustrates the key role of accurate bathymetric data plays in simulating on-going and future evolution of these important ice shelves.